ROLE OF GENDER EQUALITY, HUMAN CAPITAL, GOVERNMENT POLICIES, AND BUSINESS STRATEGIES IN IMPROVING MSME PERFORMANCE - Yesi Mutia Basri; Aji Prasetio; Taufeni Taufik; Nita Wahyuni; Gusnardi (Universitas Airlangga, 2023)
The performance or capacity of MSMEs in Indragiri Hilir Regency isexpected to decrease so that it will have a big impact on developmentand efforts to improve business performance, this problem hasresulted in a decrease in business transactions so it hashave an impact on profits or profits for businesses that are difficult to rungrowing, even many businesses are experiencing problems.bankruptcy or closure. Quantitative research is the focus of thisresearch, and basically research is to examine the influence of genderequality, human capital, government policy, and business strategyon the performance of SMEs. The sample used or used was 213 SMEsthen analyzed using warp PLS version 8.0. Result ofthe study concludes that gender equality and business strategy have apositive effect on MSME performance. Human capital andgovernment policies have a significant positive effect onMSME performance.